Structure and Anti-Inflammatory Activity of a New Unusual Fucosylated Chondroitin Sulfate from Cucumaria djakonovi - Nadezhda E. Ustyuzhanina; Maria I. Bilan; Elena G. Panina; Nadezhda P. Sanamyan; Andrey S. Dmitrenok; Eugenia A. Tsvetkova; Natalia A. Ushakova; Alexander S. Shashkov; Nikolay E. Nifantiev; Anatolii I. Usov (Marine Drugs, 2018)
Fucosylated chondroitin sulfate CD was isolated from the sea cucumber Cucumaria djakonovi collected from the Avachinsky Gulf of the eastern coast of Kamchatka. Structural characterization of CD was performed using a series of non-destructive NMR spectroscopic procedures. The polysaccharide was shown to contain a chondroitin core [→3)-β-d-GalNAc-(1→4)-β-d-GlcA-(1→]n where about 60% of GlcA residues were 3-O-fucosylated, while another part of GlcA units did not contain any substituents. The presence of unsubstituted both at O-2 and O-3 glucuronic acid residues in a structure of holothurian chondroitin sulfate is unusual and has not been reported previously. Three different fucosyl branches Fucp2S4S, Fucp3S4S and Fucp4S were found in the ratio of 2:1:1. The GalNAc units were mono- or disulfated at positions 4 and 6. Anti-inflammatory activity of CD was assessed on a model of acute peritoneal inflammation in rats. About 45% inhibition was found for CD, while a structurally related linear chondroitin sulfate SS from cartilage of the fish Salmo salar demonstrated only 31% inhibition, indicating that the presence of sulfated fucosyl branches is essential for anti-inflammatory effect of chondroitin sulfates of marine origin.